Middle East in Crisis - Prof. Dr. Iram Khalid; Uzma Naz (Journal of Political Studies, 2018)
In the contemporary times, Middle East is engulfed in multiple crises ranging from contention amongst rival states to the terrorism. In addition to that, insurgencies, civil wars and proxies, a very active role of non-state actors as well as extra regional players have become a constant feature while defining Middle Eastern politics. This research study would analyze these conflicts from multiple perspectives that include economic, social and demographic structures that contributed in ignition of the crises in Middle East. Furthermore, the incongruence amongst various actors in Middle East severed and aggravated the crises that Middle East is facing in current era. This research study argues that a comprehensive and multilateral approach is required to resolve these issues, which are affecting Middle East.